2014
DOI: 10.1002/pmic.201400194
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous dissection and comparison of IL‐2 and IL‐15 signaling pathways by global quantitative phosphoproteomics

Abstract: Common γ-chain family of cytokines (IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21, where IL stands for interleukin) are key regulators of the immune homeostasis that exhibit pleiotropic biological activities and even sometimes redundant roles as a result of the utilization of the same receptor subunit. However, they also exert distinct functions that make each of them to be indispensable. For instance, all family members can act as T-cell growth factors; however, we found that IL-15 but not IL-7 can replace IL-2 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 57 publications
(78 reference statements)
2
34
0
2
Order By: Relevance
“…We and others have previously demonstrated that IL-2, or its closely related family member IL-15, is required for promoting the proliferation of Kit225 T cells (29,53). In the present study we aimed to investigate the role of ACLY in IL-2-mediated T-cell growth.…”
Section: Acly Plays a Key Role In Il-2-dependent Proliferation Of Kitmentioning
confidence: 93%
“…We and others have previously demonstrated that IL-2, or its closely related family member IL-15, is required for promoting the proliferation of Kit225 T cells (29,53). In the present study we aimed to investigate the role of ACLY in IL-2-mediated T-cell growth.…”
Section: Acly Plays a Key Role In Il-2-dependent Proliferation Of Kitmentioning
confidence: 93%
“…In these studies, Osinalde and co-workers utilized SILAC labeling and high resolution MS combined with phosphotyrosine immunoprecipitation [91][92][93] and TiO2 enrichment of the phosphopeptides [94,95] to demonstrate that the signaling pathways activated by IL-2 and IL-15 are very similar [94,95]. In addition, they combined antibody-and TiO2-based enrichment with SILAC labeling before MS analysis to show that serine/threonine phosphorylation of the scaffold protein Gab2 is an important step in regulating IL-2 signaling [96] Quantitative phosphoproteomics has also been used to characterize CD8+ CTLs in detail [97,98].…”
Section: Proteomic Studies On T Cellsmentioning
confidence: 99%
“…Hain zuzen ere, aurreko lan batean sakon aztertu genituen zitokinak T-zeluletan sustatzen dituen seinalizazio-sareak IL-2ren eraginez fosforilatzen diren proteinak masa-espektrometria bidez aztertuz [20,21].…”
Section: Nola Eragiten Du 2-interleukinak T-zelulen Nukleoko Proteineunclassified
“…Emaitzak bat etorri ziren eskala handian egiten diren fosfoproteomika-esperimentuen emaitza ohikoekin [21,33,34,36] eta ikusi genuen, antzemandako aminoazido gehienen fosforilazio maila berdintsu mantentzen dela kitzikatutako zein kitzikatu gabeko T-zeluletan (4.irudia, puntu grisak). Halere, azpimarratu beharra dago ehunka aminoazidoren fosforilazio maila nabarmen aldatu zela IL-2rekin EKAIA, 32 (2017) Nerea Osinalde 3. irudia.…”
Section: Irudia T Linfozitoen Nukleoan Identifikatutako Fosfoserinakunclassified